Evaluation of the Effect of Chronic Fatigue Syndrome on Activities of Daily Living in Breast Cancer Patients: Breast Cancer - KUBAT BAKIR, GIZEM; goktas, sonay; yılmaz, Cem (Göbeklitepe Medical Science Journal, 2023)
Objective: This study was carried out to evaluate the effect of chronic fatigue syndrome on activities of daily living in patients with breast cancer. Method: It is a descriptive and cross-sectional study. The research was carried out in a private hospital in Istanbul between October 2016 and December 2018. The population of the study consisted of 217 patients. A separate method was not used while determining the sample of the study. The entire population also constituted the sample, and all of the patients who agreed to participate in the study were included in the sample. In this context, 112 patients were reached between October 2016 and December 2018. As a data collection tool in the research; “Personal Information Form” and “Nottingham Extended Activities of Daily Living Index” were used. The obtained data were analyzed using the SPSS program. Results: All of the patients were female, in the middle-advanced age group (56.53±13.56). 45,4% of the patients were diagnosed with invasive ductal CA, 6.3% were diagnosed with prolonged fatigue, 8% with idiopathic chronic fatigue, and 75% with chronic fatigue syndrome. Activities of Daily Living Index total score was 26.47±18.40. The correlation between chronic fatigue syndrome and activities of daily living was found to be very strong, negative and significant with r=-0.929 (p<0.05). It was determined that when the level of fatigue increased, activities of daily living decreased significantly (p<0,05). Conclusion: It was concluded that the high level of fatigue affects the daily living activities of the patients negatively. Keywords: Breast cancer, nursing care, activities of daily living, chronic fatigue syndrome